Effects of low-calorie and different weight-maintenance diets on IgG glycome composition - Deriš, Helena; Tominac, Petra; Vučković, Frano; Briški, Nina; Astrup, Arne; Blaak, Ellen E.; Lauc, Gordan; Gudelj, Ivan (Frontiers in Immunology, 2022)
Obesity-induced inflammation activates the adaptive immune system by altering immunoglobulin G (IgG) glycosylation in a way to produce more pro-inflammatory antibodies. IgG glycome has already been well studied and its alterations correlate with high body mass index (BMI) and central adiposity. Still, IgG N-glycome susceptibility to different dietary regimes for weight control after the initial weight loss has not been studied. To explore changes in IgG glycosylation induced by weight loss and subsequent weight-maintenance diets, we analyzed 1850 IgG glycomes from subjects in a dietary intervention Diogenes study. In this study participants followed a low-calorie diet (LCD) providing 800 kcal/d for eight weeks, followed by one of five weight-maintenance diets over a 6-month period. The most significant alteration of the IgG N-glycome was present eight weeks after the subjects underwent LCD, a statistically significant decrease of agalactosylated and the increase of sialylated N glycans. In the follow-up period the increase in glycans with bisecting GlcNAc and the decrease in sialylated glycans were observed. Those changes were present regardless of diet type and we did not observe significant changes between different diets. However, it should be noted that in all five diet groups there were individuals that prominently altered their IgG glycome composition in either pro-inflammatory, or anti-inflammatory directions.